Assessing the Effects of Length, Slope and Distance between Piles on the Bearing Capacity of a Pile Group under Axial Loading in Granular Soil - Firoozfar, A.; Rostami, A.; Ghaderi, H.; Zamani, H.; Rostamkhani, A. (Engineering, Technology & Applied Science Research, 2017)
Piles are usually made of steel, concrete, reinforced concrete or wood, used to enhance the ground’s bearing capacity in order to enable the construction of deep foundations, also called pile foundations. However, the exact effect of the complex interaction between the piles and the surrounding soil has not adequately been investigated yet. Considering the increased application of the technique recently, further analysis is essential for achieving the highest economic and technical capacity. Using fewer piles or shorter piles and allowing greater distances between pile groups, results to reduced construction. However, other restrictions such as high groundwater level, bedrock depth and the limited size of the foundation are also to be considered. The issue of optimal pile layout is further investigated in the current paper employing Plaxis, a finite element software, for modeling purposes and considering axial loadings in granular soils. Results are shown and further discussed.